Characterization of blast resistance in a diverse rice panel from sub-Saharan Africa - Mutiga, Samuel Kilonzo; Orwa, Philemon; Ng'ang'a, Everlyne M.; Kyallo, Martina M.; Rotich, Felix; Gichuhi, Emily W.; Kimani, John M.; Mwongera, David T.; Were, Vincent M.; Yanoria, Mary Jeanie; Murori, Rosemary; Mgonja, Emmanuel M.; et al. (Scientific Societies, 2023)
There is a recent unparalleled increase in demand for rice in sub-Saharan Africa, yet its production is affected by blast disease. Characterization of blast resistance in adapted African rice cultivars can provide important information to guide growers and rice breeders. We used molecular markers for known blast resistance genes ( Pi genes; n = 21) to group African rice genotypes ( n = 240) into similarity clusters. We then used greenhouse-based assays to challenge representative rice genotypes ( n = 56) with African isolates ( n = 8) of Magnaporthe oryzae which varied in virulence and genetic lineage. The markers grouped rice cultivars into five blast resistance clusters (BRC) which differed in foliar disease severity. Using stepwise regression, we found that the Pi genes associated with reduced blast severity were Pi50 and Pi65, whereas Pik-p, Piz-t, and Pik were associated with increased susceptibility. All rice genotypes in the most resistant cluster, BRC 4, possessed Pi50 and Pi65, the only genes that were significantly associated with reduced foliar blast severity. Cultivar IRAT109, which contains Piz-t, was resistant against seven African M. oryzae isolates, whereas ARICA 17 was susceptible to eight isolates. The popular Basmati 217 and Basmati 370 were among the most susceptible genotypes. These findings indicate that most tested genes were not effective against African blast pathogen collections. Pyramiding genes in the Pi2/9 multifamily blast resistance cluster on chromosome 6 and Pi65 on chromosome 11 could confer broad-spectrum resistance capabilities. To gain further insights into genomic regions associated with blast resistance, gene mapping could be conducted with resident blast pathogen collections.[Formula: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .